A simplified and reliable LC–tandem mass spectrometry method for determination of ulipristal acetate in human plasma and its application to a pharmacokinetic study in healthy Chinese volunteers. (22nd June 2020) - Peng, Chun; Zhao, Shunbo; Tang, Ling; Wang, Keli; Wang, Yan; Ding, Li
Abstract: In this study, a simplified, sensitive and reliable LC–tandem mass spectrometry method was established and validated for the quantification of ulipristal acetate (UPA) in human plasma and for the investigation of pharmacokinetic profile of UPA following a single oral administration of ella (UPA 30‐mg tablet) in healthy Chinese volunteers. Plasma samples were analyzed after being processed by protein precipitation with methanol. Chromatographic separation was performed on a Kinetex EVO C18 column (2.1 × 50 mm, 2.6 μm) using gradient elution with a mobile phase composed of methanol and water containing 2 mm ammonium acetate and 0.3% formic acid at a flow rate of 0.3 mL/min. The chromatographic running time was 4.0 min per sample. The MS detection was performed via an LC system with the positive ion electrospray ionization interface in multiple reaction monitoring mode using the transition of m/z 476.2 → 134.1 for UPA and m/z 479.3 → 416.2 for UPA‐d3 [internal standard (IS)], respectively. UPA and IS were monitored without severe interference from the biological matrices. The method was linear over the wide concentration range of 0.300–300 ng/mL. The intra‐ and inter‐day precision and accuracy were well within the limits required for bioanalytical assays. The method was first used to describe the pharmacokinetic characteristic of UPA after a single oral administration of ella in healthy Chinese volunteers. Based on a between‐study comparison, there were statistically significant differences ( p  < .05) between Chinese and Caucasian volunteers for the systemic exposure of UPA, suggesting that race seems to significantly impact the systemic exposure of UPA.